The Formation of Marginal Groups (Sociological Studies of Prostitution) - Acus, Arūnas (Sociologija. Mintis ir veiksmas, 2001)
The provision of sexual favours for financial reward has probably been institutionalized in the form of prostitution in every society that has had a coinage. It has nearly always involved the prostitution of women to men, though male prostitution, especially to male clients, is not uncommon. K.Davis proposed a functional theory which saw prostitution as a safety-valve, helping maintain the respectability of marriage. In Lithuania prostitution itself is illegal, soliciting in public, brothel-keeping, procuring, and living on the “immoral earnings” of a prostitute are all illegal too. Sociological studies of prostitutes show that their motivations is mainly economic and it seems likely that the number of prostitutes increases when there are fewer other job opportunities for women. International movements of prostitutes are nearly always from poor countries to richer ones. The commonest ways of working are as a street-walker, as an individual call-girl or working in illegal brothels. Studies show too, that most of clients are “Mr. Average”, there are a number of single men who have difficulties relating to women, who go to prostitutes quite frequently.